Efficient Enantiodifferentiation of Carboxylic Acids Using BINOL-Based Amino Alcohol as a Chiral NMR Solvating Agent - Li, Gaowei; Ma, Minshan; Wang, Guifang; Wang, Xiaojuan; Lei, Xinxiang (Frontiers in Chemistry, 2020)
A new optically active BINOL-amino alcohol has been designed and synthesized as chiral NMR solvating agent for enantioselective recognition. Analysis by 1 H NMR spectroscopy demonstrated that it has excellent chiral discriminating properties and offers multiple detection possibilities pertaining to proton signals of diagnostic split protons towards carboxylic acids and nonsteroidal anti-inflammatory drugs (12 examples). The nonequivalent chemical shifts (up to 0.592 ppm) of various types of protons of these mandelic acids were evaluated with the assistance of well-resolved 1 H NMR signals in most cases. In addition, enantiomeric excesses (ee) of the o-chloro-mandelic acid with different optical compositions have been calculated based on integration of well-separated proton signals.